Cardiac disease mechanobiology: advances using hiPSC-CMs - Stephanie, Georgina Aluoch; Vander Roest, Alison Schroer (Frontiers in Cardiovascular Medicine, 2025)
Cardiovascular diseases (CVDs) remain the leading cause of mortality worldwide. Despite advances in diagnosis and treatment, there is a critical need for sophisticated models that accurately reflect human cardiovascular pathophysiology. This mini review explores recent advancements in cardiac microenvironment engineering for modeling cardiac mechanobiology and investigating genetic and acquired cardiac diseases. Cardiac function relies heavily on mechanical cues, with integrin- and cadherin-based adhesion complexes mediating mechanosensitive signaling that drives disease progression. However, studying these processes in humans remains challenging. Although animal models have been indispensable, they often fail to recapitulate human-specific cardiac features. Human-induced pluripotent stem cells (hiPSCs) have been transformative, enabling patient-specific modeling and the identification of disease-specific phenotypes that are challenging to replicate in traditional animal models. Despite their promise, hiPSC-CMs are constrained by their immature phenotype and heterogeneity, which limits their efficacy in modeling adult cardiac physiology. Emerging in vitro systems, particularly those engineered using biomaterials such as hydrogels, address these limitations by mimicking the mechanical and biochemical environment of native cardiac tissue. We discuss the potential and challenges of these hiPSC-derived cardiomyocytes (hiPSC-CMs) in modeling cardiac mechanotransduction, focusing on the interplay between mechanical stress and cellular maturation, mechanics, and signaling. By integrating advanced biomaterials and genome editing technologies, these in vitro platforms hold the potential to revolutionize cardiac research, offering the prospect of more precise interventions and improved patient outcomes.